OYSTER PRODUCTION AND MEAT YIELD IN Crassostrea spp (BIVALVIA: OSTREIDAE) IN PINAR DEL RIO, CUBA - Mazón-Suástegui, José Manuel; Betanzos-Vega, Abel; Capetillo-Piñar, Norberto; Latisnere-Barragán, Hever; Ortiz-Cornejo, Nadia Livia (Ecosistemas y Recursos Agropecuarios, 2018)
The main fishing enterprise located in the province of Pinar del Río, Cuba, markets oyster meat packed in brine bags of 460 g. The oysters come from natural bank fisheries (mangrove and bottom oyster), and from farms (mangrove oyster). Although the capture during 2009 – 2013 showed an increasing trend (50 to > 80 t), the oyster meat yields recorded values below (3.3 – 3.9 %), the acceptable minimums (4.9 %); in addition, a decrease in meat weight was observed between the packaging and commercialization, impacting productivity. The objectives of the study were the assessment of oyster exploitation based on the meat yield, and to assess the meat loss in the final packed product. A monthly and annual yield variation analysis and their relationship between fishery type and oyster size was performed. Meanwhile, the loss of meat was analyzed by different treatments of oyster / brine proportions. Significant differences (p < 0.05) of meat yield (%) by oyster species and size with a better performance in the farmed oysters were observed. The traditional proportion of packing for commercialization (meat / brine, 391 g / 69 g = 460 g), influenced the weight-loss of meat by leakage of interstitial fluid. After the treatments with different proportions of meat / brine, the proportion 1:1 showed the least loss of meat weight. The breach of commercial size and the lack of cleanliness of the oysters before the shell removing process, impacted the meat yield analysis during 2009-2013